Pengaruh Internal Service Quality dan Workload terhadap Job Satisfaction Di RS Xyz Bojonegoro - Arya Ganesha Sutantio; Yohana F. Cahya Palupi Meilani (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
Introduction: One of the major factors in the success of a hospital is its employees, as a hospital contains many professionals that contribute greatly to the overall quality of service of the hospital. Thus, it is important for a hospital to maintain the Job Satisfaction of its employees, an employee that is motivated with their job would be more likely to be motivated and productive, resulting in better services given to the external customer of the hospital. Aim: This study was conducted to determine the effect of Internal Service Quality and Workload on Job Satisfaction. Methods: In this study, the data is collected using a questionnaire to 140 health workers in RS XYZ, Bojonegoro Regency using purposive sampling method. The analysis is done using partial lease square-structural equation modeling and carried out using SmartPLS software version 4.0. Results: The result of this finding is that both independent variables, Internal Service Quality and Workload have positive and negative correlation respectively. Conclusion: According to the result, providing a good Internal Service Quality to hospital employees would increase their job satisfaction, it is also important to manage workload appropriately as excessive workloads could lead to lower job satisfaction.